2006
DOI: 10.1381/096089206777822331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bariatric Surgery on the Six-Minute Walk Test in Severe Uncomplicated Obesity

Abstract: Weight reduction in the obese increases the functional capacity during walking. The improvements are refected in the patients' own assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
58
2
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 20 publications
17
58
2
10
Order By: Relevance
“…However, the OG covered a greater distance during the tread6MWT compared to the CPX, which may be attributed to the self-selection of walking speed and lower physical requirements. Regarding the submaximal test, several studies have demonstrated shorter 6MWT distances covered by obese individuals, with an increase in distances after weight loss and/or aerobic training 6,12 .…”
Section: Comparison Between Cpx and Tread6mwt Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the OG covered a greater distance during the tread6MWT compared to the CPX, which may be attributed to the self-selection of walking speed and lower physical requirements. Regarding the submaximal test, several studies have demonstrated shorter 6MWT distances covered by obese individuals, with an increase in distances after weight loss and/or aerobic training 6,12 .…”
Section: Comparison Between Cpx and Tread6mwt Outcomesmentioning
confidence: 99%
“…However, given the increasing recognition of the value of functional capacity assessments in numerous populations in conjunction with acknowledgement of the difficulty in broadly applying CPX, there is a need for valid and reliable exercise testing assessments that can be implemented in a time-and costefficient manner 3 . The six-minute walking test (6MWT) is a well-established functional assessment 4 that may provide a reasonable estimation of functional capacity in obese patients 5,6 , even with associated diseases 7 . However, more work is needed in this area to validate initial findings.…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery has been found to improve the distance walked during the six minute walk test (6MWT) [4][5][6]. One of the purposes of this study was to find out whether this could be shown in a Swedish population of women.…”
Section: Introductionmentioning
confidence: 96%
“…So far, the 6MWT has been used mainly in patients with chronic heart failure and pulmonary diseases to evaluate prognosis and treatment efficacy (16)(17)(18)(19). Few studies have been performed in obese subjects (20)(21)(22). Studies in obese children, adolescents, and adults show a high degree of reproducibility, indicating that the test is suitable for obese individuals as a group (23,24).…”
Section: Introductionmentioning
confidence: 99%